Body composition analysis according to the exercise modality in adults with obesity: Pilot study - Liliana Aracely Enríquez del Castillo; Natanael Cervantes Hernández; Ramón Candia Luján; Luis Alberto Flores Olivares (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
Obesity has generated a pandemic in relation to public health; however, depending on the type of exercise, intensity, frequency, and time spent exercising, it provides different effects on the human body. The present investigation has the objective of comparing the effect of two modalities of exercise, aquatic and grounded, on the body composition of overweight and obese adults. The present was an experimental study with 26 overweight and obese adults distributed in two exercise groups: aquatic and grounded. Both groups received 12 weeks of moderate intensity aerobic training assessed with a heart rate monitor and determined through the maximum heart rate on each individual grounded and aquatic training. The study variables were Body Mass Index (BMI), fat percentage, and lean mass. After carrying out the exercise program significant differences were observed in the reduction of BMI as well as in the percentage of fat in both sexes ( < 0.01). No differences were observed in relation to BMI reduction, nor the percentage of fat evaluated before and after by different exercise modalities; likewise, there was no difference in either sex. In conclusion, exercise provides favorable changes in body composition variables; however, in this study, it does not rely on the exercise modality.